2002
DOI: 10.1088/1126-6708/2002/01/019
|View full text |Cite
|
Sign up to set email alerts
|

Some exact results on the matter star-product in the half-string formalism

Abstract: We show that the D25 sliver wavefunction, just as the D-instanton sliver, factorizes when expressed in terms of half-string coordinates. We also calculate analytically the star-product of two zero-momentum eigenstates ofx using the vertex in the oscillator basis, thereby showing that the star-product in the matter sector can indeed be seen as multiplication of matrices acting on the space of functionals of half strings. We then use the above results to establish that the matrices ρ 1,2 , conjectured by Rastell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…The geometrical picture we have found of the sliver singularities ties in neatly with previous calculations [4,6,15] which have shown that the sliver states factorize into a product of gaussians of the left-and right-string oscillators r 2k+1 , l 2k+1 of the form…”
Section: Jhep01(2002)004supporting
confidence: 82%
See 2 more Smart Citations
“…The geometrical picture we have found of the sliver singularities ties in neatly with previous calculations [4,6,15] which have shown that the sliver states factorize into a product of gaussians of the left-and right-string oscillators r 2k+1 , l 2k+1 of the form…”
Section: Jhep01(2002)004supporting
confidence: 82%
“…Recently, certain solutions of the matter string field equations, known as sliver states [2,3,4], have received much attention [5]- [15]. In this paper we make some simple observations regarding the structure of these sliver states.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A proposal for such vacuum string field theory (VSFT) was made in [4], and investigated in [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Using these two descriptions the sliver states and their generalizations are studied in [163,168,169,171,172]. In these lectures (Section 4) we will discuss the half-string formalism with main focus on the operator description of the matter sector.…”
Section: String Field Theorymentioning
confidence: 99%